Performance analysis of emulated software defined wireless network - Tsehay Admassu Assegie (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Software defined wireless network is a networking architecture and an emerging networking principle that is based on software defined network. A software defined network is a fundamental networking concept which separates the networking devices used in communication network form the program that runs on the top of these devices. In this paper we will explore the modeling tools used for software defined wireless network in our literature survey and based on the survey we have used mininet-Wi-Fi for modeling software defined wireless network, which is the best and most widely used emulation tool for software defined wireless network. Lastly, we have evaluated the performance of TCP traffic bandwidth for different number of emulated end stations and access points.